Pemetrexed-induced lipodermatosclerosis: clinical course and management of a rare cutaneous toxicity - Kahlon, Navkirat; Vallepu, Shirisha; Gowda, Anusha Manje; Baddam, Sujatha (Current problems in cancer. Case reports, 2025)
We present the case of a 67-year-old male with stage IV lung adenocarcinoma who developed pemetrexed-induced lipodermatosclerosis (LDS) and a flare of polymyalgia rheumatica (PMR) during chemotherapy treatment. Initially misdiagnosed as cellulitis, the patient experienced progressive skin toxicity that was ultimately recognized as LDS, associated with pemetrexed. The management of PMR flares and LDS was complex, requiring steroid therapy adjustments and the introduction of pentoxifylline. This case highlights the need for awareness of chemotherapy-induced skin toxicity and the challenges of managing underlying autoimmune conditions in cancer treatment.